Impacts of a Micro-Enterprise Clustering Program on Firm Performance in Ghana - Jörg Peters; Maximiliane Sievert; Christoph Strupat (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Widely considered as an important backbone of economies in developing countries, micro- and small enterprises face several constraints in doing business in Ghana. The creation of industrial zones (IZ) with improved access to infrastructure and secured land tenure is a potential remedy to promote local economic development. In this paper, we assess the effects of an intervention on business performance that establishes or upgrades IZs for micro- and small enterprises in Ghana based on firm-level data on 227 enterprises. Lacking reliable baseline data and an appropriate control group, we use retrospective questions to reconstruct the situation before the intervention. Furthermore, in order to account for general changes in the local economic environment, we examine regional agricultural market development over time. The results show that the establishment of IZs leads to the creation of new firms, but for existing firms that relocated to the IZs the effects on firm performance are negative. – – Ein bedeutendes Merkmal der Wirtschaft in Ghana ist der hohe Anteil an Kleinunternehmen. Die Produktivität dieser Unternehmen ist oft aufgrund mangelnder Infrastruktur (Elektrizität, Wasser, Straßen) und unsicherer Landbesitzverhältnisse eingeschränkt. In dieser Studie wird untersucht, inwieweit die Einrichtung oder Verbesserung von Gewerbezonen diese Probleme vermindert und die Produktivität der Unternehmen beeinflusst. Dazu wurden Informationen von 227 kleinen Unternehmen aus drei Gewerbezonen erhoben. Wir nutzen retrospektive Fragen, um die Unternehmenssituation vor dem Umzug in die neuen Gewerbezonen zu rekonstruieren. Die Ergebnisse unserer Analyse zeigen, dass die Einrichtung von Gewerbezonen zu mehr Unternehmensgründungen führt und umgezogene Unternehmen nicht von der Maßnahme profitieren.
Keywords: O14; O22; L69; 330; project evaluation; firm clustering; micro-enterprises